Engajamento do consumidor em uma comunidade virtual de marca - Lima, Vitor Moura (2014)
The objective of the research was the investigation of the consumer engagement in a virtual brand community, which considered L'Oréal Paris Brasil Facebook Fan Page as a context of observation. On this purpose, by a netnography method, the interactions were collected from members of the website over three months and analyzed from the perspective of the conceptual model presented by Brodie et al. (2011b). During content analysis, which considered Bardin (2007) techniques, the dimensions, processes and sub-processes of the consumer engagement were identified, as proposed by the conceptual model. In addition, the results point to the validation of the model and reinforce the view that the mere participation or involvement doesn't indicates engagement, because it reflects a complex psychological state, context dependent and requires antecedents and consequences processes. Based on these findings, theoretical and practical implications, as well as suggestions for future studies, are discussed.